(3QSGdI aj abg GdMLs - (3GdTGej GdYGedj, CHh efUhQ, GHf GdTgjO GdKGfj, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj GdTGej GdYGedj, J (B1011(3g` (B1602(3es ((3fGUQ Hf YHO Gddg Hf fGUQGdHMQGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj aQV ML GdHjJ Ydi ef GSJWGY Edjg SHjdG (B... (3gPg fHPI ef GdcdGe aj abg GdML Edi HjJ Gddg GdMQGes
(3BNQgG (B:s
(3BNQgG(B: (3hGJee dj EfYGec Efc NjQ GdefYejf hGLYd HGbj YeQj aj GdML hGdYeQI hGHJZGA hLgc jG QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 192s
(3GdPQjYI, L (B22: 162s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis